Hubungan Nilai Ankle Brachial Index Dengan Kualitas Hidup Penderita Diabetes Melitus Tipe 2 - Liana Safitri; Fahrun Nur Rosyid (Jurnal Berita Ilmu Keperawatan, 2018)
One complication of Type 2 Diabetes Mellitus that affects the peripheral nervous system is Peripheral Artery Disease (PAD). PAD can be detected by checking the Ankle Brachial Index (ABI). PAD diagnostic tests with greater ABI accuracy are likely to reflect changes in a person's quality of life related to the conditions experienced. The purpose of this study was to determine the relationship between ABI values with the quality of life of people with DM. This type of research is analytic (survey) using a cross sectional approach. The sample used in this study were 44 type 2 DM patients in the Surakarta City branch of Persadia. The sampling technique used was purposive sampling. The instrument used to record data using a questionnaire, sphygmomanometer and stethoscope. Based on the analysis using the Chi-Square test, the value of p = 0.010 (p